Moroccan EFL students’ attitudes toward higher education reform: A TPB-based quantitative study - Laabidi, Hicham; Lahnech , Chaimaa (Universitas Ahmad Dahlan, 2025)
The rapid evolution of the educational field demands continuous adaptation and reforms to meet the changing needs of students and society. Recognizing this necessity, this study investigates freshmen EFL students’ attitudes towards a newly implemented higher educational reform and identifies areas of support and concern regarding the new curriculum changes. Understanding these attitudes is crucial for the successful adoption and long-term impact of this reform. This study aims to examine freshmen EFL students’ attitudes toward the reform and pinpoint areas of support and concern. A comprehensive survey involving 217 students was administered, with their responses analyzed across multiple dimensions including anxiety, confidence, liking, and perceived usefulness of the reform. The findings reveal that while the overall attitude towards the reform is positive, with a mean score of 3.9370, there are significant concerns about specific aspects, such as the removal of the Final Year Project (FYP). Neutrality regarding the reform's impact on job market readiness was also noted among a notable segment of students, reflecting uncertainty. Based on these results, it is recommended to enhance practical skills integration, offer structured orientation programs, and establish continuous feedback mechanisms to ensure the reform meets students’ needs effectively.